SISTEM INFORMASI BERBASIS WEB PADA TOKO BUKU DI TOKO BATAM - Purba, rehni jayana; Tukino, Tukino (Computer Science and Industrial Engineering, 2021)
Developments in the field of technology can be used to help work, one of which is by building a web-based information system at a used bookstore in the city of Batam. The sales system in this bookstore is still manual, where buyers have to come to the store to get the desired book. Limitations in terms of product marketing are one of the obstacles in the bookstore. The main problem at this bookstore is the difficulty of buyers when looking for books because of the low stock of books. The data collection method Used on this examine is to apply commentary and interview techniques, where researchers come to the location to make observations to see the existing system in the bookstore and interview the owner to find out the existing problems. The research technique utilized in this study is the System Development Life Cycle (SDLC) method with the waterfall model. By making this online sales system, it can make its easier for sellers to market products, and for buyers to be able to see the available stock of books and choose and buy books without having to come to a bookstore